Out of Place (Gwalia): Occasional Essays on Australian Regional Communities and Built Environments in Transition. (March 2016) - Pinto, Sarah
Abstract : Out of Place (Gwalia): Occasional Essays on Australian Regional Communities and Built Environments in Transition. Edited by Philip Goldswain, Nicole Sully, and William M. Taylor (Perth: UWA Publishing, 2014), pp.xi + 311. AU$39.99 (pb).